Engineering, Ecological and Social Monitoring of the Largest Underwater Sculpture in the World at John Brewer Reef, Australia - Adam Smith; Al Jayson Songcuan; Nathan Cook; Rachelle Brown; Kailash Cook; Reuben Richardson (Journal of Marine Science and Engineering, 2022)
The largest underwater sculpture in the world, the ‘Coral Greenhouse’ by artist Jason deCaires Taylor, was commissioned by the Museum of Underwater Art and installed at John Brewer Reef, Australia, in December 2019. The planning process required certified engineering design drawings associated with design life, durability and suitability of materials, and baseline ecological surveys. Following approval, the operational phase required annual monitoring of substrate, ecology, social values, and marine debris. We geo-referenced three permanent transects and designed a before/after rapid monitoring assessment of substrate, fish, and invertebrates. Substrate surveys indicated 11% concrete and 89% sand. Fish surveys indicated significant increases of diversity and abundance, with 12 species and 65 individuals recorded in 2018 compared to 46 species and 365 individuals recorded in 2022. Macroinvertebrate species maintained no significant trends in abundance, species richness, and diversity with respect to time between 2018 and 2022. We monitored coral restoration and natural recruitment at the site, measuring aesthetics, survivorship of planted corals, and coral recruitment. Of 131 corals transplanted in March 2020, survivorship was 100% at 1 month, 92% at 6 months, and 91.6% at 12 months. Hard and soft corals were recruited to the structure at a density of 8.35 hard corals/m2 and 10.9 soft corals/m2 over 26 months.